Electropharmacogram of Sceletium tortuosum extract based on spectral local field power in conscious freely moving rats. (11th January 2016) - Dimpfel, Wilfried; Schombert, Leonie; Gericke, Nigel
Abstract: Ethnopharmacological relevance: The endemic succulent South African plant, Sceletium tortuosum (L.) N.E. Br. (synonym Mesembryanthemum tortuosum L.), of the family Mesembryathemaceae, has an ancient oral tradition history of use by San and Khoikhoi people as an integral part of the indigenous culture and materia medica . A special standardized extract of Sceletium tortuosum (Zembrin®) has been developed and tested pre-clinically in rats, and clinically in healthy subjects. Aim of the study: The present investigation aimed at the construction of electropharmacograms of Zembrin® in the presence of three dosages (2.5, 5.0 and 10.0 mg/kg), and comparative electropharmacograms and discriminatory analyses for other herbal extracts, citicoline and rolipram. Material and methods: Seventeen adult Fischer rats were each implanted with a set consisting of four bipolar concentric steel electrodes fixed by dental cement and three screws driven into the scalp. After two weeks of recovery from surgery the animals were adapted to oral administration by gavage and to experimental conditions (45 min pre-drug period and 5 h of recording after a rest of 5 min for calming down). Data were transmitted wirelessly and processed using a Fast Fourier Transformation (FFT). Spectral power was evaluated for 8 frequency ranges, namely delta, theta, alpha1, alpha2, beta1a, beta1b, beta2 and gamma power. Results: Zembrin® dose dependently attenuated all frequency ranges, to varying degrees. The most prominent was the statistically significant reduction in alpha2 and beta1a waves, correlated with activation of the dopaminergic and glutamatergic transmitter systems respectively. This feature is common to all synthetic and herbal stimulants tested to date. The second strongest effects were reduction in both the delta and the theta frequency ranges, correlated with changes in the cholinergic and norepinephrine systems respectively, a pattern seen in preparations prescribed for neurodegenerative diseases. Theta wave reduction in common with the delta, alpha2 and beta1 attenuation has been noted for analgesic drugs. Attenuation of alpha1 waves emerged during the highest dosage in all brain areas, a feature seen in all antidepressants. Discussion: The electropharmacogram of Zembrin® was compared to the electropharmacograms of herbal extracts archived in our database. Extracts of Oenothera biennis and Cimicifuga racemosa gave a very similar electropharmacograms to that of Zembrin®, and extracts of Ginkgo biloba and Rhodiola rosea gave rather similar electropharmacograms to Zembrin®. Linear discriminant analysis confirmed these similarities and demonstrated that all three dosages of Zembrin® plotted in close neighbourhood to each other. Citocoline, a synthetic compound originally developed for cognitive enhancement, had a similar electropharmacogram to Zembrin®. Similarity to the electropharmacograms of the synthetic phosphodiesterase-4 inhibitor, rolipram, suggests Zembrin® has antidepressant and cognitive function enhancing potential. Conclusion: The combined results from the electropharmacograms and comparative discriminatory analyses suggest that Zembrin® has dose dependent activity, with potential applications as a cognitive function enhancer, as an antidepressant, and as an analgesic. Graphical abstract: